Design and construction of a ferrocene based inclined polycatenated Co-MOF for supercapacitor and dye adsorption applications. Issue 34 (15th August 2017) - Rajak, Richa; Saraf, Mohit; Mohammad, Akbar; Mobin, Shaikh M.
Abstract : An inclined polycatenated Co-MOF (1 ) synthesized by a facile slow-diffusion technique shows excellent performance for supercapacitors and dye adsorption. Abstract : A new cobalt based inclined polycatenated metal–organic framework, [Co4 (FcDCA)4 (bpy)4 (H2 O)6 ]·11H2 O n [FcDCA = 1, 1′-ferrocene dicarboxylic acid and bpy = 4, 4′-bipyridyl] (1 ), has been designed and synthesized in a facile manner.1 can be simplified as a 2D + 2D → 3D inclined polycatenation class with Doc1/1, as authenticated by single crystal X-ray studies. Further, 1 was employed as a modifier for a glassy carbon electrode (1-GCE ) without using any binders to explore its supercapacitor performance. Detailed electrochemical investigations carried out using1-GCE reveal a specific capacitance of 446.8 F g −1 at a current density of 1.2 A g −1, with an excellent cycle life of ∼88.37% (after 800 cycles). Moreover, a high rate performance was also observed for1-GCE (it retains 81% of its initial capacitance up to a high current density of 10 A g −1 ), which endorsed its good stability on the electrode surface. The results were found to be superior than those for [Co(bpy)1.5 (NO3 )2 ] n (2 ), highlighting the role of the presence of FcDCA in1 . Additionally, the notable adsorption and desorption properties of1 towards selected Chicago Sky Blue (CSB) and Congo Red (CR) dyes confirms the candidature of1 as a potential dye adsorbing agent.